Human Rights Challenges in the Contemporary World. Reflections on a Personal Journey of Thought and Action - Lafer, Celso (HannahArendt.net, 2016)
Following the steps indicated by Hannah Arendt regarding the epistemological role of experience, Celso Lafer, discusses how his experiences as professor, as a Human Rights lawyer and as Brazilian Public Official shaped his views regarding Human Rights. He examines the challenges in the contemporary world that the Human Rights agenda faces in the national and international sphere. His organizing perspective is a broad and heuristic use of Hannah Arendt’s “The Right to have Rights”. He stresses and exemplifies that the proper access of individuals and groups to an effective legal order is a key variable to enable the containment of the nullification and impairment of Human Rights.